Pemodelan Daya Pengadukan selama Proses Dehidrasi Osmotik Irisan Mangga dalam Larutan Gula - Leopold O. Nelwan; Fibula Yudisaputro; Hiroshi Nabetani (Jurnal Keteknikan Pertanian, 2015)
This study discusses mathematical model of agitation power due to the change of sugar solution concentration during the process of mango slices osmotic dehydration. The sugar solution agitation was performed in several levels of rotational speed to correlate the power number with the Reynolds number. Then, the obtained model was used to calculate the power consumption for various temperature and initial rotational speed of shaft. The results showed that the correlation can be used for various conditions of shaft rotational speed and solution concentration. Osmotic dehydration for 8 hours at conditions of 30-50OC with rotational speed of 143-525 rpm results in solution dilution from 61OBx to 50.5-52.5OBx. Temperature of 30OC with initial shaft rotational speed of 500 rpm results in power consumption ten times higher than that of 50OC and 148 rpm. Moreover, power consumption reduction up to 80% of initial energy consumption due to the dilution of the sugar solution during the osmotic dehydration process was obtained.